The Effect Of Motivation And Work Discipline On Performance Of Tasikmalaya Branch Post Office Employees - Siska Suryani; Kusuma Agdhi Rahwana; Arga Sutrisna (Penerbit Jurnal Indonesia, 2022)
This study aims to determine and analyze the effect of motivation and discipline partially and simultaneously on the performance of the Tasikmalaya Branch Post Office employees. The method used in this study is a quantitative method with a consumer survey approach with a sample of 89 respondents. The data collected in the form of data is done by using a questionnaire technique. Analysis of the data in this study using multiple regression analysis, correlation coefficient and coefficient of determination using SPSS version 26 software. The results show that motivation and work discipline simultan eously and partially affect employee performance.